Changes in the Fish Fauna Associated with Soft Bottom during El Niño – La Niña (98-99) in a Coastal Lagoon, on the Pacific Coast of Baja California Sur, Mexico - Emelio Barjau-González; Abril Karim Romo-Piñera; Juan Manuel López-Vivas; José Ángel Armenta-Quintana (Research Advances in Environment, Geography and Earth Science Vol. 7, 2024)
During the warm period of El Niño in the spring and fall of 1998, the average water temperatures were very close, between 21.1 and 20.9°C (± 0.2°C); However, in the summer of 1998 the average was higher (24.3°C), in contrast, during the cold period of La Niña in the winter season of 1999 an average of 13.4°C was recorded. The composition of fish fauna of San Ignacio Lagoon comprised 44 species. Eight species were present during all seasons: Eucinostomus dowii, Hippocampus ingens, Pleuronichthys guttulatus, Paralabrax maculatofasciatus, Paralichthys californicus, Sphoeroides annulatus, Sphoeroides lispus and Urobatis halleri. The species with the highest abundance during El Niño were: Paralabrax maculatofasciatus, Eucinostomus dowii; whereas during La Niña they were: Sphoeroides lispus, Paralabrax auroguttatus and Sphoeroides annulatus. In relation to zoogeography affinity in fishes, the provinces and regions were: the Panamic (37%), Californian (32%), Eastern Pacific (18%), Mexican (11%), and the Cortez province (2%). The fish species of tropical affinity found during the El Niño event in 1997-1998 were: Hoplopagrus guntheri, Eucinostomus gracilis, Exerpes asper, Achirus mazatlanus, Rhencus panamensis, Cyclopsetta panamensis, Bairdiella icistia, Microlepidotus inornatus, Orthopristis reddingi, Sphoeroides lispus, and Urobatis maculatus.